Studi Evaluasi Penerapan Pembelajaran Daring pada Masa Pandemi Covid-19 di SD Negeri 4 Kota Bengkulu - Yolanda Yolanda; Alexon Alexon; panut setiono (JURIDIKDAS, 2022)
This study aims to evaluate the application of online learning during the Covid-19 pandemic at State Elementary School 4 Bengkulu City which includes 1) Online learning planning; 2) Implementation of online learning; and 3) Assessment of learning outcomes during online learning. This study is an evaluative assessment using the Discrepancy Model. The subjects of this study were the principal, teachers and students. Quantitative data was obtained from the results of the observation sheet score and qualitative data obtained from the results of the Observation Sheet, Interview, and Documentation. The data analysis technique used is data analysis according to Miles and Hubernan and observational data analysis using the formula for the average score, the highest score, the lowest score, the difference in scores and the range of values for each criterion. The results show that the average evaluation 1) Online learning planning gets a score of 3.2 with a sufficient category 2) The implementation of online learning gets an average score of 3 with a sufficient category 3) Assessment of learning outcomes during online learning gets an average score 3 with sufficient category. The overall evaluation results show an average score of 3.0 with a sufficient category. In planning aspects that are in accordance with Circular Letter Number 15 of 2020 are preparing lesson plans, learning media, learning methods, and learning resources. Furthermore, the implementation of learning aspects that are in accordance with Circular Letter Number 15 of 2020 are greetings, checking student attendance, giving assignments, feedback, and reports, and reminding students and parents to collect. Then, the assessment of online learning outcomes that are in accordance with Circular Letter Number 15 of 2020 are the summative and formative assessment aspects. Thus, the application of online learning at the Bengkulu City 4 State Elementary School has met the sufficient criteria.